Lost in translation: Reflexive thematic analysis in research with Pacific peoples - Rangiwai, Byron; Enari, Dion; Masae, Christina; Paea, Daniel; Tahilanu-Mapili, Lavinia; Vailahi, Veronica (Te Kaharoa, 2021)
This paper reflects on reflexive thematic analyses with Pacific peoples from different cultural and language backgrounds. This paper will briefly describe reflexive thematic analysis according to Braun et al. (2019) and reflect upon issues concerning thematic analysis and Pacific cultures and languages. As academics, researchers, and practitioners, “we engage in a co-construction of knowledge” with our communities while adhering to cross-cultural notions of respect (Enari & Rangiwai, 2021, p. 2). We draw upon our collective cultural knowledge to offer a unique insider perspective (Enari & Rangiwai, 2021) concerning our current understandings of reflexive thematic analysis as it applies to research with Pacific peoples.